Simulation of High Performance Quantum Well GaN-based LED - Hassan, Z.; Zainal, N.; Hashim, M. R.; Abu Hassan, H. (2005)
The performance of quantum well GaN/A1GaN light emitting diode (LED) is reviewed for three different barrier compositions; symmetric barrier composition with low A1 content, asymmetric barrier composition with higher A1 content on p-type cladding layer and lower A1 content on n-type clading layer, and symmetric barrier composition with higher A1 content. The study was conducted using ATLAS/BLAZE & LUMINOUS software developed by Silvaco International Inc. Integrated radiative recombination rate was studied on applied voltages up to 5V. Results showed three phases of LED performance with different applied voltages and these were explained using badgap theory. I-V characteristic for each design agrees with the total additional voltage drop equation for a quantum well structure. The dominant radiative recombination rate regions in LED at low and high supplied voltages are also presented for the best performance LED design.